MODEL INDIKATOR KINERJA PROYEK PADA SEKTOR BANGUNAN PERUMAHAN BERTINGKAT TINGGI REGIONAL D.K.I. JAKARTA - Redaksi Tim Jurnal (FORUM MEKANIKA, 2018)
Successful projects require an increase in project performance to maintain development aesthetics and productivity. Civil Engineer needs to know the indicators in improving project performance. The research aims to identify key performance indicators that include quality, cost, and time criteria in the contractor's perspective and models of indicators that have a significant influence on the project of regional high-rise residential using Structural Equation Modeling (SEM) - Partial Least methods Square (PLS). The study was used a questionnaire survey. Questionnaires containing performance indicators were developed using a fishbone diagram approach and verified through interviews with experts in construction projects. The result used to determine the level of importance of indicators with the SEM-PLS method. The results show 40 performance indicators identified in the study. All indicators are grouped in 5 criteria, namely: Human Resources, equipment, material, work methods, and finance. The results of the SmartPLS calculation show a model with 18 main indicators that have an influence on project performance on the criteria of cost, quality and time. Three indicators with the highest level of influence are Training of workers on a regular basis, Complying with K3 when working in the field, and Multi-level supervision according to the project organizational structure.